Psikoedukasi Komunikasi Verbal dan Teknik Penyuluhan Interaktif melalui Media Buku Saku bagi Petugas BNNP Sumatera Selatan Bidang P2M - Rina Oktaviana; Alya Salsabila (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Drug abuse remains a serious problem in Indonesia, affecting public health, social life, productivity, and community security. Preventive efforts require effective educational programs supported by the communication skills of outreach officers. This community service activity aimed to improve the understanding of officers from the Prevention and Community Empowerment Division (P2M) of the National Narcotics Agency of South Sumatra Province regarding verbal communication and interactive counseling techniques. The method employed was psychoeducation through lectures, interactive discussions, question-and-answer sessions, and the distribution of a pocketbook as an educational medium and practical guide. The results showed that the pocketbook helped enhance officers' understanding of effective communication and the application of interactive counseling techniques. Participants provided positive feedback, stating that the material was concise, systematic, and relevant to field practice. This activity is expected to improve the quality of drug abuse prevention counseling by making information delivery more communicative, participatory, and effective.